The use of palm oil clinker as a sustainable construction material: A review - Hamada, Hussein M.; Jokhio, Gul A.; Al Attar, A.A.; Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Humada, Ali Mahmood; Gul, Yasmeen (Elsevier, 2020)
Waste byproducts of palm oil can potentially help preserve non-renewable resources and enhance the sustainable, environmental, and economic characteristics of the construction industry if used as alternative construction materials. Palm oil clinker (POC) is a waste byproduct of palm oil mills, which is obtained after burning the solid palm oil waste for producing electricity. Recently, significant research has focused on the usage of POC as lightweight concrete aggregate. The present paper presents and examines the physical and chemical properties of POC as well as the mechanical properties of palm oil clinker concrete (POCC). POC has a lower specific gravity than the conventional weight aggregates, thus it has low density that enables the weight of the resulting concrete to reduce. The concrete containing POC would have a lower density as well as compressive strength than the normal aggregate concrete. The present review is significant for the future studies to identify the knowledge gaps and address the shortfalls in other aspects. In addition, this paper could be a base knowledge for researchers to encourage them to use green and sustainable materials that have great benefits to the environment and cost less if compared with the conventional materials.